Knowledge and perception of pregnant women to episiotomy in Ibadan. (2017)
Background: Episiotomy is the most common obstetric procedure for prevention of perineal laceration during childbirth. In order to further involve women in the decision-making process for their care, understanding their perception of common obstetric procedures will contribute to practical discussions on the gaps that need to be filled. Methods: Cross-sectional descriptive survey of consenting pregnant women attending antenatal clinic at the University College Hospital, Ibadan. Information on their socio-demographic data, knowledge and perception about episiotomy was obtained using an interviewer-administered questionnaire. Data analysis was done with SPSS version 18.0. Results: A total of 304 women were interviewed, of which 199 (65.5%) had ever heard about episiotomy. Among those ever heard, 62 (31.2%) have had personal experience with 10 (16.1%) reporting sexual dysfunction as complication. Only 60 (19.7%) are ever willing to accept episiotomy while 172 (56.6%) will advise friends and relatives against acceptance. Only parity is significantly associated with knowledge (X2 – 15.08, p<0.001) while age is associated with previous experience (X2 – 22.92, p<0.001). Previous experience had no effect on willingness to accept repeat episiotomy (OR = 1.24; 95% CI: 0.63 – 2.44). Health workers are the main source of information. Conclusion: Parturients in our environment are yet to accept episiotomy due to inadequate information as many of them believed it is unnecessary. Sessions on intrapartum interventions in obstetrics need to be further integrated into our antenatal care services.